Environmental diplomacy : negotiating more effective global agreements - Susskind, Lawrence; Ali, Saleem H. (Saleem Hassan), 1973-; Hamid, Zakri Abdul (New York : Oxford University Press, 2014)
'Environmental Diplomacy' provides an accessible narrative on understanding the geopolitics of negotiating international environmental agreements and clear guidance on improving the current system. In this book, authors Lawrence Susskind and Saleem Ali expertly observe international environmental negotiations to effectively inform the reader on the geopolitics of protecting our planet. This second edition offers an additional perspective from the Global South as well as providing a broader analysis of the role of science in environmental treaty-making.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 28, 2014).
Keywords: Environmental law, International; Sustainable development -- Law and legislation; Negotiation -- Methodology